(untitled) (Research, Society and Development, 2022)
The law’s function of social pacification, improvement of social relations, and conflict resolution has been compromised as a result of the difficulties in accessing justice. All this compromises the guarantee of the fundamental rights of citizens. In this context, the Justice Officer is an important way as a facilitator in the process of social pacification and access to justice. Thus, the present work aimed to discuss the function of the Justice Officer as a contributor to sustainable local development in the expansion of forms of access to justice. To do so, it was used the PRISMA methodology, the systematic review in the specialized literature, considering articles published in the last 7 years, in the main scientific databases. The results obtained showed that factors such as lack of knowledge, economic issues, and confidence in the rapid resolution, imply obstacles in the search for rights by citizens. Thus, it was verified that, for the due accomplishment of the jurisdictional function, the Justice Officer can act as a facilitator and that his activity with the litigants is decisive to narrow the paths between the citizen and the Judiciary. This can be achieved through guidance and the realization of a process of self-composition, aiming to achieve the resolution of conflicts and access to justice.